Genetic Analysis: New Horizons in the Diagnosis of Genetic and Infectious Diseases - Adnan, Hawra; Ibraheem, Ayat Khalil; Fadhel, Karrar Jabbar; Alawi, Kawthar Jaafar (American Journal of Biology and Natural Sciences, 2024)
Genetic testing is one of the most significant developments in modern medicine, playing a crucial role in diagnosing both genetic and infectious diseases. By utilizing advanced techniques such as DNA sequencing and genetic fingerprinting, genetic testing can identify genetic mutations responsible for hereditary diseases or determine genetic factors that increase susceptibility to infectious diseases. Additionally, genetic testing allows for improved treatment responses, including tailoring therapies based on an individual’s genetic makeup. However, there are some technical and ethical challenges that need to be addressed, such as reducing costs, enhancing testing accuracy, and safeguarding genetic privacy.